2017
DOI: 10.1002/epi4.12082
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of waiting times for assessment and epilepsy surgery between a Canadian and a Mexican referral center

Abstract: SummaryObjectiveTo provide a comprehensive transnational overview of wait times for epilepsy surgery in Canada and Mexico.MethodsWe reviewed all cases referred for epilepsy surgery between 2007 and 2015 at the Saskatchewan Epilepsy Program Royal University Hospital (SEP) (n = 70; Saskatoon, Canada) and the National Institute of Neurology and Neurosurgery (NINN) (n = 76; Mexico City, Mexico) and compared wait times, calculated as the time from diagnosis of epilepsy on assessment at an epilepsy center to epileps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…The mean waiting time from the first visit to surgical referral for the patients in our study was 38.8 (SD 16.9) weeks, with an additional 17.2 weeks between referral to the surgical team and the first post-operative visit. This compares favorably to a 2017 Canadian and Mexican comparative study which showed the average waiting times from the first epilepsy center visit to surgery of 111.4 weeks ( n = 72) in Canada, and 182.8 weeks ( n = 81) in Mexico, versus 55.8 weeks in our study [31].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The mean waiting time from the first visit to surgical referral for the patients in our study was 38.8 (SD 16.9) weeks, with an additional 17.2 weeks between referral to the surgical team and the first post-operative visit. This compares favorably to a 2017 Canadian and Mexican comparative study which showed the average waiting times from the first epilepsy center visit to surgery of 111.4 weeks ( n = 72) in Canada, and 182.8 weeks ( n = 81) in Mexico, versus 55.8 weeks in our study [31].…”
Section: Discussionsupporting
confidence: 81%
“…The results for the age at presentation to the clinic and years living with epilepsy were similar to the Canadian and Mexican study: patient age was 36.7 and 37.4 in Canada and Mexico, respectively, versus 36.9 in our study; and years with epilepsy were 20.2 and 27.4 in Canada and Mexico respectively, versus 18.5 years in our study. The literature indicates that delays in surgical treatment are mainly due to delays in referral to specialist clinics, rather than delays in assessment and the decision to proceed to surgery once under the care of the clinic [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains a concern that patients who may benefit from the procedure are not being referred for surgery eligibility assessment in a timely manner or those who, despite being assessed as suitable surgical candidates, elect to not undergo the procedure [9][10][11][12]. Globally, studies suggest that eligible patients can live for up to 20 years or more before they receive surgical treatment [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The wait times to see a neurosurgeon are often large. In most countries, the time from diagnosis to referral to an epilepsy center ranges from 18.9 [ 1 ] to 20 years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A patient with GBM reaches the surgeon usually within a few days after diagnosis. A patient with epilepsy takes 18–20 years [ 1 , 2 ] from diagnosis to reach the surgeon in most countries. This is a problem.…”
Section: Introductionmentioning
confidence: 99%